P53 maintains gallid alpha herpesvirus 1 replication by direct regulation of nucleotide metabolism and ATP synthesis through its target genes - Xu, Li; Chen, Zhijie; Zhang, Yu; Cui, Lu; Liu, Zheyi; Li, Xuefeng; Liu, Shengwang; Li, Hai (Frontiers in Microbiology, 2022)
P53, a well-known tumor suppressor, has been confirmed to regulate the infection of various viruses, including chicken viruses. Our previous study observed antiviral effect of p53 inhibitor Pifithrin-α (PFT-α) on the infection of avian infectious laryngotracheitis virus (ILTV), one of the major avian viruses economically significant to the poultry industry globally. However, the potential link between this antiviral effect of PFT-α and p53 remains unclear. Using chicken LMH cell line which is permissive for ILTV infection as model, we revealed that, consistent with the effects of PFT-α on ILTV replication we previously reported, knockdown of p53 repressed viral gene transcription and the genome replication of ILTV effectively. The production of infectious virions was also suppressed significantly by p53 knockdown. Further bioinformatic analysis of genes with p53 binding sites revealed extensive repression of these putative p53 target genes enriched in the metabolic processes, especially nucleotide metabolism and ATP synthesis, by PFT-α administration in ILTV-infected LMH cells. Among these genes, eighteen were involved in nucleotide metabolism and ATP synthesis. Then eight of the eighteen genes were selected randomly for validations using ChIP-qPCR and RT-qPCR, all of which were successfully identified as p53 target genes. Our findings shed light on the mechanisms through which p53 controls ILTV infection, meanwhile expand our knowledge of chicken p53 target genes.